Heritage Walking: a Popular Geopolitics Study of the AYA Application and its role in Nation-Building and Heritage as a Motivational Factor for Walking - Armor, Matthew (My University, 2023)
The AYA application (hereafter, app) released by the Chickasaw Nation in 2018, is a fitness app with a gamified rewards system built around the history and culture of the Chickasaw Nation. The Chickasaw Nation as a tribal nation within the US is vulnerable to being assimilated into American culture. Therefore, looking at AYA as a nation-building tool to identify efforts by the Chickasaw government to instill their identity into citizens, is vital to help other endangered cultures. The citizenry’s own desire to learn about their heritage through a rewards system is leveraged by the developers by encouraging physical exertion in the form of walking to achieve progression in the app. However, the app is using an unproven method to reach its goals. Prior walking apps have used history as a motivator but not in tandem with a user’s own heritage sculpted by their government. Government applications are blunter in their approach to nation building, as they create apps purely focused on civic education when related to nation building. It is the combination of walking applications and nation building in AYA that makes it a unique application to test its approach towards fitness through heritage as a motivation for both. A survey was conducted to test users’ feelings towards the Chickasaw Nation and a change in their walking habits. The results show an inconclusive but slight positive correlation between the two. The nation-building aspects of AYA were examined using qualitative coding of the app’s content to discover the main themes used in crafting a heritage for the Chickasaw people to practice. This work highlights the effectiveness of new technologies in promoting national identity and fitness and how they are received when melded together.
Keywords: Gamification; Communication Geography; Nation-Building; Heritagization